Hubungan antara Persepsi Kinerja Kepolisian dengan Tingkat Kepercayaan Mahasiswa Psikologi di Universitas Muhammadiyah Surakarta - Aisyah Nur Setyaningsih; Luh Putu Shanti Kusumaningsih (Observasi : Jurnal Publikasi Ilmu Psikologi, 2026)
This study examines the relationship between students’ perceptions of the performance of the Sukoharjo Police Resort (Polres) and the level of public trust among students of Universitas Muhammadiyah Surakarta (UMS). The study employed a quantitative correlational approach to identify the relationship between the two variables. The independent variable (X) is the perception of police performance, while the dependent variable (Y) is the level of public trust in Sukoharjo Regency as represented by UMS students. A sample of 100 respondents was selected using purposive sampling based on predetermined criteria. Data were collected through a Likert-scale questionnaire and subsequently analyzed using validity and reliability tests, classical assumption tests, simple linear regression, Pearson correlation analysis, t-test, and the coefficient of determination. The conceptual framework of this study is based on Institutional-Based Trust Theory, Tom R. Tyler’s Procedural Justice Theory, and Robert Putnam’s Social Capital Theory. The findings indicate that there is a positive and significant relationship between students’ perceptions of police performance and their level of trust. These results suggest that better perceptions of police performance are associated with higher levels of public trust among UMS students.